An Examination of Employee Rewards and Work Environment on Employee Creativity and Innovation - Mdhlalose, Dickson (SEISENSE (PRIVATE) LIMITED, 2024)
Purpose - The provision of rewards to employees for their innovative ideas and creative ideas acts as a motivational factor, encouraging them to sustain their efforts in developing novel and innovative solutions. The objective of this research is to examine the effects of employee rewards and work environment on employee creativity and innovation.Design/Methodology/Approach - This research used a quasi-experimental approach (specifically, an explanatory design). This inquiry relied on secondary sources. The collection of secondary material was conducted by using multiple online search platforms and specialist journals. Research Findings - Employees' ability to be creative and innovative is bolstered by all three types of rewards: intrinsic rewards, which have a positive effect on intrinsic motivation, extrinsic non-financial rewards, and extrinsic financial rewards, which can either encourage or discourage employees' efforts to be creative and innovative. Organizational environments that promote and cultivate employee creativity and receptiveness to novel ideas are more inclined to cultivate a culture that fosters creativity and then innovation. Originality - The significance of this research study adds value to the existing corps of information about understanding the effects of employee rewards with the aid of the work environment on employee creativity and innovation. Practical Implications - Drawing from the findings of this study it has been proven that in the corporate world employees are different with various types of needs. Hence to successfully motivate them to be creative and innovative organizations must provide employee rewards that are comprehensive and at the same time must balance the employee rewards they offer with the conducive work environment with employees' individual needs.